Role of glia in K+ and pH homeostasis in the neonatal rat spinal cord - Jendelová, P; Syková, E (Glia, 1991)
Stimulation-evoked transient changes in extracellular potassium ([K+]e) and pH (pHe) were studied in the neonatal rat spinal cords isolated from 3-13-day-old pups. In unstimulated pups the [K+]e baseline was elevated and pHe was more acid than that in Ringer's solution (3.5 mM K+, pH 7.3-7.35). The [K+]e and pHe in 3-6-day-old pups was 3.91 +/- 0.12 mM and pHe 7.19 +/- 0.01, respectively, while in 10-13-day-old pups it was 4.35 +/- 0.15 mM and 7.11 +/- 0.01, respectively. The [K+]e changes evoked in the dorsal horn by a single electrical stimulus were as large as 1.5-2.5 mM. Such changes in [K+]e are evoked in the adult rat spinal cord with stimulation at a frequency of 10-30 Hz. The maximal changes of 2.1-6.5 mM were found at a stimulation frequency of 10 Hz in 3-6-day-old animals. In older animals the [K+]e changes progressively decreased. The poststimulation K(+)-undershoot was found after a single stimulus as well as after repetitive stimulation. In 3-8-day-old pups, the stimulation evoked an alkaline shift, which was followed by a smaller poststimulation acid shift when the stimulation was discontinued. In pups 3-4-days-old the stimulation evoked the greatest alkaline shifts, i.e., by as much as 0.05 pH units after a single pulse and by about 0.1 pH units during stimulation at a frequency of 10 Hz. In 5-8-day-old pups, the alkaline shift became smaller and the poststimulation acid shift increased.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Acid-Base Equilibrium; neuroglie; draslík; Spinal Cord; Potassium; intracelulární tekutina; Electric Stimulation; Neuroglia; Rats, Inbred Strains; novorozená zvířata; acetazolamid; mícha; krysa rodu Rattus; Acetazolamide; Intracellular Fluid; zvířata; chlorid hořečnatý; acidobazická rovnováha; karboanhydrasy; Animals, Newborn; homeostáza; Homeostasis; Hydrogen-Ion Concentration; Extracellular Space; Rats; Magnesium Chloride; Animals; elektrická stimulace; koncentrace vodíkových iontů; Carbonic Anhydrases; inbrední kmeny potkanů; extracelulární prostor